Acute stress amplifies experienced and anticipated regret in counterfactual decision-making. (4th July 2021) - Wu, Yin; van Dijk, Eric; Li, Hong
Abstract: Previous research has shown that stress can affect emotion processing in a variety of settings. However, little attention has been paid to the effects of stress on emotional decision-making. The present study addressed this question by exposing healthy young participants either to a stressor ( n  = 30)–socially evaluated cold pressor task– or a non-stressful control task ( n  = 30). Subsequently, participants completed a computerized decision-making task in which they could compare the obtained factual outcome with a non-obtained counterfactual outcome. Saliva samples were taken at four time points over the course of the experiment and used to analyze cortisol levels. Results revealed that acute stress induced reliable salivary cortisol increase over the experimental task. At the outcome delivery stage, acute stress amplified negative emotions induced by the counterfactual comparison. At the choice stage, under stress, participants were more likely to make regret-averse decisions. The findings that acute stress amplifies both experienced and anticipated regret is consistent with dual process frameworks such that stress tilts decision-making toward more emotional and intuitive processing. Lay summary: Stress is thought to affect emotional processing. The present study investigated the effects of acute stress on emotional decision making using a typical counterfactual decision making task. Acute stress amplified both experience and anticipation of regret, consistent with the dual process frame that stress tilts decision-making toward more emotional and intuitive processing.